2019
DOI: 10.1186/s12889-018-6358-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parasitic contamination of raw vegetables in Nakhon Si Thammarat province, southern Thailand

Abstract: BackgroundSoil-transmitted helminth (STH) infections are major public health problems in poor and developing countries that require fecal contamination of the environment for transmission. The consumption of raw vegetables without proper washing is one of the main routes of intestinal parasite acquisition. Therefore, this study was designed to detect the prevalence of intestinal parasitic contamination in commonly consumed raw vegetables sold in three central open-air markets in Nakhon Si Thammarat province, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 29 publications
10
45
4
3
Order By: Relevance
“…This study emphasizes the importance of hand hygiene to prevent parasite eggs from entering the body. Despite the report of Toxocara egg contamination in raw vegetables in Nakhon Si Thammarat Province in a previous study [26], eating fresh vegetables was not significantly associated with T. canis infection in the current study. This may be explained by the small number of schoolchildren who ate fresh vegetables (36, 20.3%); thus, contamination from vegetables was not a likely route of transmission among these children.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study emphasizes the importance of hand hygiene to prevent parasite eggs from entering the body. Despite the report of Toxocara egg contamination in raw vegetables in Nakhon Si Thammarat Province in a previous study [26], eating fresh vegetables was not significantly associated with T. canis infection in the current study. This may be explained by the small number of schoolchildren who ate fresh vegetables (36, 20.3%); thus, contamination from vegetables was not a likely route of transmission among these children.…”
Section: Discussioncontrasting
confidence: 99%
“…In Thailand, previous reports revealed that Toxocara eggs were found in the stool of dogs and cats [24,25]. Furthermore, Toxocara eggs were identified in raw vegetables from markets in southern Thailand [26]; however, their impact on humans has not been investigated. In this study, we aimed to assess the seroprevalence of Toxocara canis infection and the associated risk factors among schoolchildren in rural areas of southern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…This study emphasizes the importance of hand hygiene to prevent parasite eggs from entering the body. Despite the report of Toxocara egg contamination in raw vegetables in Nakhon Si Thammarat Province in a previous study [22], eating fresh vegetables was not significantly associated with T. canis infection in the current study. This may be explained by the small number of schoolchildren who ate fresh vegetables 36 (20.3%); thus, contamination from vegetables was not a likely route of transmission among these children.…”
Section: Discussioncontrasting
confidence: 99%
“…In Thailand, previous reports revealed that Toxocara eggs were found in the stool of dogs and cats [20,21]. Furthermore, Toxocara eggs were identified in raw vegetables from the markets in southern Thailand [22]; however, its impact on humans has not been investigated. In this study, we aimed to assess the seroprevalence and associated risk factors of Toxocara canis infection among schoolchildren in rural areas of southern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…It has also to be considered that the potential uptake of animals A. caninum eggs does not necessarily mean that relevant amounts of animals faeces need to be taken up, since eggs may have been attached to food. In fact, many studies report the presence of hookworm eggs in food 43,44 and also in water 45 . However, this a very low probability since twelve A. caninum eggs were found in the respective patient.…”
Section: Discussionmentioning
confidence: 99%